Nutrition education in colleges of education in the English-speaking Caribbean - Hamilton, Marlene A. (CANDI, 1982)
This paper discusses the findings of a survey of colleges of education in 10 Caribbean territories. Among aspects investigated were: local resources used in drawing up nutrition curricula, degree of emphasis placed on nutrition education, teaching methods employed, and teaching aids used. The results indicate an ambiguous situation with some institutions making a noteworthy contribution and others paying scant attention to the subject
Keywords: Nutrition education